(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Assisted reproductive technologies (ARTs) are widely used as a tool to improve reproductive performance in both humans and animals. In particular, in the veterinary field, ARTs are used to improve animal genetics, recover endangered animals, and produce offspring in the event of subfertility or infertility in males or females. However, the use of ARTs did not improve the fertilization rate in some animals due to various factors such as the difficulty in reproducing an anatomical and humoral substrate typical of the natural condition or due to the increase in catabolites and their difficult elimination. The in vitro environment allows the production and increase in the concentration of substances, including reactive oxygen species (ROS), which could be harmful to gametes. If produced in high concentration, the ROS becomes deleterious, both in vitro and in vivo systems. It has been seen that the use of antioxidants can help neutralize or counteract the production of ROS. The present study aims to report the latest findings regarding the use of antioxidants in ARTs of some domestic species, such as dogs, cats, and horses, compared to other animal species, such as cattle, in which ARTs have instead developed more widely. J. Adv. Vet. Anim. Res., 8(1): 173-184, Mar 2021 http://doi.org/10.5455/javar.2021.h500